Who walks into vape shops in Southern California?: a naturalistic observation of customers. Issue 1 (December 2016) - Sussman, Steve; Allem, Jon-Patrick; Garcia, Jocelyn; Unger, Jennifer; Cruz, Tess; Garcia, Robert; Baezconde-Garbanati, Lourdes
Abstract Background The rising popularity of electronic cigarettes (e-cigarettes) has been accompanied by the proliferation of vape shops in the United States. Vape shops are devoted to the sale of e-cigarettes and e-juices. This study aimed to describe the age, gender, and ethnicity of customers who frequent these shops, determine whether conversations transpire between retailers and customers, as well as identify the types of activities taking place while customers are inside the store. Methods A naturalistic observation study of 186 customers in 59 vape shops in Southern California was completed in locations that were relatively high in Korean, Non-Hispanic white, Hispanic, or African American ethnicity. Results Across all shops, the average estimated age of customers was 30.29 years old (SD = 9.70), 53 % were estimated to be non-Hispanic white, and 79 % were males; few minors entered the shops. Conversations about vaping related topics were prevalent (e.g., sampling e-juices, receiving help on hardware, and talking about vaping). Purchases were commonly observed as well as customers lounging in the shop. Conclusion Vape shops provide consumers a place to purchase and discuss e-cigarettes and offer an environment that serves as a place of recreation with customers lounging once inside. Findings should inform local tobacco control efforts and regulatory policies in the future.